2015
DOI: 10.11113/jt.v73.4337
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Forecasting Methods Used in Real Estate Housing Price Modelling

Abstract: Forecasting is very fundamental in real estate where the past transactions become the evidences while decision making for the present and the future. Several techniques and validation approached that were commonly used in housing price index forecasting. Beside the appropriate forecasting method, error calculation is one of the critical constraints in accuracy out of all methods. This paper overview the available methods and the types of error being considered in forecasting techniques. Then the forecasting me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The strength and similarity of the model capacity in both countries showed that each market signal correctly predicts turning points in the economy for as much as 75% (Nigeria) and 80% (South Africa) of the time. The misclassification rate for the Nigerian logistic model is, however, 5% higher which is similar to the average model error margins observed by Munusamy, Muthuveerappan and Baba [14]. Meanwhile, the classification accuracy of the South African logit model is higher than that of the Nigerian logit model.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The strength and similarity of the model capacity in both countries showed that each market signal correctly predicts turning points in the economy for as much as 75% (Nigeria) and 80% (South Africa) of the time. The misclassification rate for the Nigerian logistic model is, however, 5% higher which is similar to the average model error margins observed by Munusamy, Muthuveerappan and Baba [14]. Meanwhile, the classification accuracy of the South African logit model is higher than that of the Nigerian logit model.…”
Section: Discussionsupporting
confidence: 80%
“…A lot of research has been carried out to promote macroeconomic modelling as a means of improving forecasting accuracy. Some popular works in these subject areas include studies such as those of Munusamy, Muthuveerappan and Baba [14]; Jadevicius, Sloan and Brown [15]; Tsolacos [16]; Jadevicius, Sloan and Brown [17]; and Boshoff [4]. Buehler and Almeida [18] discussed the investment market in the United States relative to predicting commercial market bubbles as a part of decision making for global investors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation